HLA-DR, and not PLA2R, is expressed on the podocytes in kidney allografts in de novo membranous nephropathy - Wen, Jiqiu (Medicine (Baltimore), 2016)
Idiopathic membranous nephropathy (IMN) is known to be associated with antibodies acting on the M-type phospholipase A2 receptor (PLA2R) of the podocyte. However, the mechanism underlying de novo membranous nephropathy (dn MN) posttransplantation remains unclear. In this study, we aimed to elucidate the mechanism underlying dn MN. We selected 8 cases with dn MN and compared them to 20 IMN cases. Fifteen cases of stable grafts were selected as controls. Several differences between the dn MN group and the IMN group were detected. IgG4 showed negligible positive staining in patients with dn MN, while it was predominant in the IMN group (1/8 vs 20/20, P < 0.001). Serum anti-PLA2R antibodies and anti-PLA2R antibodies of the podocyte were very few in the dn MN patients; however, these antibodies were detected in most of the IMN patients (serum anti-PLA2R antibodies: 1/8 vs 16/20, P = 0.002, anti-PLA2R antibodies of the podocyte: 0/8 vs 17/20, P < 0.001). The dn MN patients also showed higher ratio of interstitial inflammation, peritubular capillaritis, and peritubular capillary C4d deposition. Importantly, human leukocyte antigens (HLA)-DR expression was detected on the podocytes in most of the dn MN patients, but none of the IMN patients and stable graft patients showed HLA-DR expression. These data suggested that the PLA2R pathway, which is known to play a role in IMN, was not involved in the mechanism underlying dn MN. On the contrary, dn MN might be associated with the alloimmune response directed against the podocyte.